The international law of human trafficking - Gallagher, Anne; Cambridge (Online service). (New York Cambridge University Press, 2010)
Although human trafficking has a long and ignoble history, it is only recently that trafficking has become a major political issue for states and the international community and the subject of detailed international rules. This book presents the first-ever comprehensive and in-depth analysis of the international law of human trafficking. Anne T. Gallagher calls on her direct experience working within the United Nations to chart the development of new international laws on this issue. She links these rules to the international law of state responsibility as well as key norms of international human rights law, transnational criminal law, refugee law, and international criminal law, in the process identifying and explaining the major legal obligations of states with respect to preventing trafficking, protecting and supporting victims, and prosecuting perpetrators. This is a timely and groundbreaking work: a unique and valuable resource for policymakers, advocates, practitioners, and scholars working in this new, controversial, and important field.
Electronic reproduction.
Keywords: Human trafficking; Human trafficking -- Prevention -- International cooperation; Electronic books